The Influence of Career Development and Startup Ecosystem Support on the Retention of Gen Z Entrepreneurs in the Digital Startup Ecosystem - Fitria, Novy; Muttaqien, Fauzan; Rizki, Via Lailatur; Dewi, I Gusti Ayu Panca; Permadi, I Komang Oka; Nguyen, Thanh Lam (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
This study examines the influence of career development and startup ecosystem support on the retention of Generation Z digital entrepreneurs in Indonesia. The increasing involvement of young people in digital entrepreneurship raises the need to understand the factors that enable them to maintain long-term entrepreneurial engagement. Using an explanatory quantitative approach, data were collected through structured questionnaires and analyzed with multiple linear regression to identify the role of individual development and ecosystem support. The results indicate that career development contributes to strengthening entrepreneurial commitment by enhancing clarity of goals, competence, and confidence, while startup ecosystem support provides essential external reinforcement through networks, mentoring, collaboration, and resource access. The interaction of both factors shows a complementary effect in sustaining entrepreneurial involvement. This study concludes that the retention of Gen Z digital entrepreneurs is shaped by a combination of internal developmental processes and external ecosystem support, and it offers practical implications for educators, incubators, and policymakers in strengthening digital entrepreneurship programs.